Early Acute Kidney Injury in Stroke Patients Submitted to Endovascular Treatment: A Cohort Study - Oliveira, M (2024)
Background/Objectives: Acute kidney injury (AKI) is a potential complication of cardiovascular disorders and is associated with worse outcome. The aim of this study was to assess the incidence of early AKI after endovascular therapy for acute ischemic stroke, identify predictors for this complication, and test the association between AKI and mortality or death or dependency. Methods: This was a single-center cohort study involving consecutive patients with acute ischemic stroke submitted to endovascular therapy between 2015 and 2022. AKI was defined according to the KDIGO criteria and evaluated at 48 h. Other outcomes of interest were vital status and functional dependency at 3 months using the modified Rankin Scale, with death or dependency being defined as a score > 2. An adjustment for potential confounders was performed using logistic regression. Results: Overall, 1150 patients were included in the analysis, with a mean age of 74 years and a slight female preponderance (56%). The median NIHSS was 15, the mean onset-to-groin time was 392 min, and 92% of patients were successfully recanalized. The overall incidence rate of AKI was 6%. On univariate analysis, patients with AKI were older (p = 0.002), had a longer time to EVT (p = 0.042), higher NIHSS (p = 0.006), higher blood glucose (p = 0.033), and lower baseline glomerular filtration rate (GFR) (p < 0.001). After adjustment for confounders, AKI was independently associated with NIHSS (p = 0.012), time to treatment (p = 0.004), and lower baseline GFR (p < 0.001). AKI was also independently associated with higher mortality (OR = 2.302, p = 0.003). Conclusions: Patients with impaired baseline renal function and more severe stroke are at higher risk of AKI, and AKI begets worse stroke outcome. Better strategies are required to optimize treatment outcome in these patients and avert this vicious cycle.